Obesity in patients with COVID-19: a systematic review and meta-analysis - Huang, Yi; Lu, Yao; Huang, Yan-Mei; Wang, Min; Ling, Wei; Sui, Yi; Zhao, Hai-Lu (Metabolism, clinical and experimental, 2020)
Obesity is common in patients with coronavirus disease 2019 (COVID-19). The effects of obesity on clinical outcomes of COVID-19 warrant systematical investigation. This study explores the effects of obesity with the risk of severe disease among patients with COVID-19. Body mass index (BMI) and degree of visceral adipose tissue (VAT) accumulation were used as indicators for obesity status. Publication databases including preprints were searched up to August 10, 2020. Clinical outcomes of severe COVID-19 included hospitalization, a requirement for treatment in an intensive care unit (ICU), invasive mechanical ventilation (IMV), and mortality. Risks for severe COVID-19 outcomes are presented as odds ratios (OR) and 95% confidence interval (95%CI) for cohort studies with BMI-defined obesity, and standardized mean difference (SMD) and 95%CI for controlled studies with VAT-defined excessive adiposity. A total of 45, 650 participants from 30 studies with BMI-defined obesity and 3 controlled studies with VAT-defined adiposity were included for assessing the risk of severe COVID-19. Univariate analyses showed significantly higher ORs of severe COVID-19 with higher BMI: 1.76 (95%: 1.21, 2.56, P = 0.003) for hospitalization, 1.67 (95%CI: 1.26, 2.21, P<0.001) for ICU admission, 2.19 (95%CI: 1.56, 3.07, P<0.001) for IMV requirement, and 1.37 (95%CI: 1.06, 1.75, P = 0.014) for death, giving an overall OR for severe COVID-19 of 1.67 (95%CI: 1.43, 1.96; P<0.001). Multivariate analyses revealed increased ORs of severe COVID-19 associated with higher BMI: 2.36 (95%CI: 1.37, 4.07, P = 0.002) for hospitalization, 2.32 (95%CI: 1.38, 3.90, P = 0.001) for requiring ICU admission, 2.63 (95%CI: 1.32, 5.25, P = 0.006) for IMV support, and 1.49 (95%CI: 1.20, 1.85, P<0.001) for mortality, giving an overall OR for severe COVID-19 of 2.09 (95%CI: 1.67, 2.62; P<0.001). Compared to non-severe COVID-19 patients, severe COVID-19 cases showed significantly higher VAT accumulation with a SMD of 0.49 for hospitalization (95% CI: 0.11, 0.87; P = 0.011), 0.57 (95% CI: 0.33, 0.81; P<0.001) for requiring ICU admission and 0.37 (95% CI: 0.03, 0.71; P = 0.035) for IMV support. The overall SMD for severe COVID-19 was 0.50 (95% CI: 0.33, 0.68; P<0.001). Obesity increases risk for hospitalization, ICU admission, IMV requirement and death among patients with COVID-19. Further, excessive visceral adiposity appears to be associated with severe COVID-19 outcomes. These findings emphasize the need for effective actions by individuals, the public and governments to increase awareness of the risks resulting from obesity and how these are heightened in the current global pandemic. •Obesity increases risk for hospitalization among patients with COVID-19.•Obesity increases risk for needing ICU admission among patients with COVID-19.•Obesity increases risk for requiring IMV support among patients with COVID-19.•Obesity increases risk for death among patients with COVID-19.•Excessive visceral adiposity appears to be associated with severe COVID-19 outcomes.